Utilization of indigenous pH control agents for drilling fluid preparation - Nnaemeka Princewill Ohia; Henry Ndilemeni; Stanley Toochukwu Ekwueme (Zaštita Materijala)
Drilling fluid pH is an important factor in drilling and production operations. If the pH is acidic, this will cause metallic parts such as the drilling string and casings to corrode. Also, much more additives will be needed to achieve the right rheological properties. In this work, the suitability of agro waste such as oil palm fruit fibre, ripe plantain peels and unripe plantain peels as drilling fluid pH control agents was studied. The materials were gotten from local sources and subjected to drying, burning and filtration. The filtrates obtained were used to treat water based drilling mud. It was found that the oil palm fruit fibre solution raised the pH to 8, while the ripe and unripe plantain peels solutions raised the pH values to 10 respectively. Laboratory test for sodium and potassium contents on the locally prepared pH control additives showed significantly higher concentrations in the unripe plantain peel solution, thereby making it most suitable as a pH control agent compared to the others.